O corvo que rima também sabe jogar: tradução intersemiótica e design de jogo - Krasnoschecoff, Andrêi (Universidade Federal de São Carlos, 2023)
Electronic games emerged in the 1950s. Over time, the novelty became a kind of cultural phenomenon, resulting, on the one hand, in the creation of an industry that moves a lot of money, and on the other, in a cultural practice that influenced and was influenced by various spheres of human activity. Thibault (2016) understands that games emerged in a borderline position of culture and over time began to occupy a central position. This movement takes place within the semiosphere, a concept developed by Lotman (2014) to explain cultural semiotic behavior. Languages have been merging as technology has developed. Within this cultural flow, translations take place. Translation, here, will be treated as an everyday phenomenon of language, as we are using the theoretical ideas of Peirce's semiotics (2018) and the Semiotics of Culture, which place translation in a different place than what is usually thought. The current importance of electronic games within the dynamic system of culture was what motivated this experimentation to produce an intersemiotic translation, whose source text is a poem (The Raven, written by Edgard Allan Poe) and the result is a document with a script and guidelines for creating an electronic game. In this process, we bring the translator's view: the problems he encounters and the attempt to solve them. It is expected to contribute both to the reach of the work and the author to different audiences and discussions about the translation and interaction between electronic games and other media.
The raven that rhymes also knows how to play: intersemiotic translation and game design
Keywords: Tradução intersemiótica; Jogos eletrônicos; O Corvo; Edgar Allan Poe; Intersemiotic translation; Electronic games; The Raven; LINGUISTICA, LETRAS E ARTES::LINGUISTICA